KEPEMILIKAN SAHAM, KEBIJAKAN DIVIDEN, KARAKTERISTIK PERUSAHAAN, RISIKO SISTIMATIK, SET PELUANG INVESTASI DAN KEBIJAKAN HUTANG - Yulius Kurnia Susanto (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The purpose of the research was to obtain empirical evidence that managerial and institutional ownership, divide nd policy, firm growth, profitability, firm size, systematic risk, investment opportunity set and asset structure affect debt policy. The population in this research are all companies that listed in Indonesia Stock Exchange with the observation period 2005 to 2008. The sample selection was done by using purposive sampling method. Data used in this research was obtained from financial statement and Fact Book, performance summary of listed companies and BAPEPAM - LK . Data analysis used a multiple regression analysis. The results of this research are managerial ownership, cash dividend policy, profitability, firm size, investment opportunity set and asset structure affect debt policy. While the institutional ownership, firm growth and systematic risk not affect debt policy. Manager who owns shares in his company tends to use funds from retained earnings and share capital. They will distribute cash dividends to attract in - vestors to buy shares. Source of funds from obligation providing a risk to the company.